Man-made canals as a hotspot of aquatic macrophyte biodiversity in Slovakia - Dorotovicova, Csilla (Limnologica, 2013)
Today, canals are the integral parts of agricultural land in Central Europe. In Slovakia they comprise 15% of all flows. Here I investigated the macrophyte flora of nine canals in Slovakia representing three different types in relation to environmental variables. A total of 102 plant species (32 hydrophytes, 13 amphiphytes and 57 helophytes) and non-specified algae filamentosae were recorded, including three neophytes and 24 endangered species in Slovakia. The investigated environmental variables explained 23% of the variability in macrophyte species composition. The best explanatory variables were the land-use type, water conductivity, channel morphometry, bank structure and sediment type, with the last two highly correlated to each other. Compared to natural streams, canals differ in terms of channel morphometry, water regime and management. Though canals are eutrophic and have relatively uniform channels, their species diversity is surprisingly high (11–62 species), which is comparable or even higher than in natural waters. As most drainage canals are subject to low intensity management, their environmental conditions resemble streams with low hydrologic dynamics. Substantial differences have been recorded in canals with higher nutrient load and in canals with a specific function. In conclusion, canals, as surrogate biotopes and biocorridors organically connected with natural flows, may be important components of aquatic biodiversity.